2018
DOI: 10.17707/agricultforest.64.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on the Annual Water Balance in a Humid Climate

Abstract: Lithuania and Bosnia and Herzegovina are considered as countries with high vulnerability and low adaptive capacity to cope with climate change. The entire territory of these countries is characterized by the warming trend, with positive trends in both the maximum and the minimum temperatures throughout the year. The increase in air temperature has resulted in change of evapotranspiration and mean annual water balance values. These countries are also frequently faced with an occurrence of severe droughts and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…AET can be a measure of agricultural water productivity, these results indicate an improvement of general conditions for agricultural production in the central -mountainous region of BiH. Thus, Climate change may have a positive effect on the yield in this area (Čadro et al, 2018;Radusin et al, 2016), and in same time negative effect on the rest of the country (north and south). Such positive effect also found in similar studies, especially for the northern Europe (Jacob et al, 2018), while the rest of Europe, especially the Mediterranean region, will mostly be negatively affected (Behrens et al, 2010).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…AET can be a measure of agricultural water productivity, these results indicate an improvement of general conditions for agricultural production in the central -mountainous region of BiH. Thus, Climate change may have a positive effect on the yield in this area (Čadro et al, 2018;Radusin et al, 2016), and in same time negative effect on the rest of the country (north and south). Such positive effect also found in similar studies, especially for the northern Europe (Jacob et al, 2018), while the rest of Europe, especially the Mediterranean region, will mostly be negatively affected (Behrens et al, 2010).…”
Section: Resultsmentioning
confidence: 75%
“…Increase of potential evapotranspiration (PET) and soil moisture deficit (SMD) was found for Banja Luka, Tuzla, Zenica and Mostar (Čadro et al, 2016). Increasing trends in reference evapotranspiration, runoff and soil moisture deficit and decreasing trend in the amount of the snow were found for the Sarajevo located in central part of BiH (Čadro et al, 2018;.…”
Section: Introductionmentioning
confidence: 89%
“…The above observations are in accordance with the predictions of Vucijak et al (2014), who consider that in the future in Bosnia and Herzegovina, due to climate change, there will be an increase in the frequency of extreme weather events such as an increase in temperature, lack of precipitation, and an increase in floods. The assumption is that due to such climate changes, the yields of traditional agricultural crops will decrease (Cadro et al, 2018). On the other hand, due to the increase in temperature, optimal conditions are created for the growth and development of plants originating from warm climates.…”
Section: Discussionmentioning
confidence: 99%
“…However, our research showed that some benefits could be reaped in practice. Despite the current and expected future increases in global temperature due to climate change (Cadro et al, 2018), the conditions in this country are good for basil growth (temperatures are still not above the optimum range) (Gavrić et al, 2021). Basil can grow under the agro-ecological conditions of Bosnia and Herzegovina and thus be regarded as an alternative to species that are sensitive to high summer temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation